Aktualisasi Budaya Organisasi Dalam Meningkatkan Pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kota Batam - Indriani, Anju; Epriadi, Dedi (SCIENTIA JOURNAL, 2021)
Public services in Indonesia are still faced with conditions that are not in accordance with the needs and changes in various fields of social life. The purpose of this research is to find out how the actualization of organizational culture in improving services at the Batam City Population and Civil Registration Service. In this research, the researcher used a qualitative research method with a descriptive approach and uses two data sources, namely primary data sources and secondary data sources. Services at the Batam City Population and Civil Registration Service were established based on Batam City Regional Regulation (Perda) Number 1 of 2015 concerning the Implementation of Population Administration in Batam City. In practice, service activities in the Population Move-in section of the Batam City Population and Civil Registration Service are considered not optimal and have not run perfectly, this is because several inhibiting factors have been found, such as cultural differences between the indigenous people of Batam City and immigrant communities from outside Batam City, the management that is considered rigid and takes a long time, employees do not have the space to further optimize individual creativity and innovation, limited facilities and infrastructure, facilities that are less comfortable.